The effect of melatonin on the lipid levels in menopausal women: A double-blind, controlled, clinical trial - Nehleh Parandavar; Mohsen Hojat; Khadijeh Abdali; Sara Keshtgar; Masoumeh Emamghoreishi; Babak Shirazi Yeganeh (Wolters Kluwer Medknow Publications, 2018)
BACKGROUND: Cardiovascular diseases are the major public health problem in many countries and are responsible for more than half of the deaths in above 50-year-old women. The most common curable risk factor of these disorders is hypoestrogenemia resulting from menopause. The present study aimed to investigate the effect of melatonin on plasma lipid levels in menopausal women. MATERIALS AND METHODS: The present double-blind, placebo-controlled, clinical trial was conducted in 2013-2014 on 240 menopausal women between 40 and 60 years old referring to the Gynecology and obstetrics clinics of Shiraz University of Medical Sciences who were randomly divided into two groups. The intervention group received 3 mg melatonin tablets and the control group received the placebo for 3 months. The data were gathered using the demographic information questionnaire and lipid profile test before and 3 months after the intervention. Then, the data were analyzed through the SPSS statistical software (version 16). The repeated measures analysis of variance, the least significant difference, the independent-sample t, the Chi-square, and Fisher's exact tests were done for data analysis. RESULTS: The two study groups were similar regarding the demographic and clinical variables at the beginning of the study. In the melatonin group, the amount of triglyceride increased from 140.34 ± 48.29 before the study to 151.24 ± 54.60 3 months after the intervention and no significant difference was observed between the two groups in this regard (confidence interval [CI] = 95%, P > 0.05). In addition, no significant difference was found between the two groups concerning low-density lipoprotein cholesterol level (CI = 95%, P = 0.125). CONCLUSION: Melatonin was not effective in reduction of lipid levels. However, further controlled studies are needed to be conducted on the issue.